Optimization of 2D sparse array antenna for FMCW radar - Mohd. Isa, Farah Nadia; Mohd. Ramli, Huda Adibah; Ismail, Ahmad Fadzil (IEEE, 2016)
This paper is a study on optimizing a 2D sparse array antenna that has been developed for the application of avalanche radar. The fully populated array of 144 elements (16 × 9) is analysed and some of the prominent result are tabulated in this paper findings. The antenna element used is a directive YagiUda microstrip antenna. The method used for this study is purely heuristical and based on the findings of previous analysis that has been carried out by the author. It is shown that with the right choice of antenna elements thinning, the beampattern of the phased array antenna could be controlled to give the desired pattern for the users.